Birmingham’s Women Poets: Aestheticism and the Daughters of Industry - Marion Thain (Cahiers Victoriens et Edouardiens)
British female aestheticism is seen to have a key geographical locus in London, and critics have convincingly argued over recent years for the importance of that city and its rich cultural life to the work of late-nineteenth-century women’s poetry. Yet it is seldom recognised that the aesthetic London lifestyle of these writers was in key instances only made possible by family fortunes amassed through the industrial expansion of Birmingham and its surrounding conurbation. Looking at A. Mary F. Robinson, the two women who wrote as “Michael Field”, and Constance Naden (all of whom established themselves in London but were either born in the Midlands or whose parents lived and worked there), this essay argues for a web of personal, ideological, intellectual and economic connections around Birmingham and the Midlands, which was central to aestheticism. In doing so, this essay not only uncovers an unacknowledged part of the narrative of British aestheticism, it also disrupts some of the convenient critical boundaries which have become entrenched within our study, and which currently limit its scope.